Lead Catalyzed GaAs Nanowires Grown by Molecular Beam Epitaxy - Igor V. Shtrom; Nickolai V. Sibirev; Ilya P. Soshnikov; Igor V. Ilkiv; Evgenii V. Ubyivovk; Rodion R. Reznik; George E. Cirlin (Nanomaterials)
This study investigates the growth of gallium arsenide nanowires, using lead as a catalyst. Typically, nanowires are grown through the vapor–solid–liquid mechanism, where a key factor is the reduction in the nucleation barrier beneath the catalyst droplet. Arsenic exhibits limited solubility in conventional catalysts; however, this research explores an alternative scenario in which lead serves as a solvent for arsenic, while gallium and lead are immiscible liquids. Liquid lead easily dissolves in Si as well as in GaAs. The preservation of the catalyst during the growth process is also addressed. GaAs nanowires have been grown by molecular beam epitaxy on silicon Si (111) substrates at varying temperatures. Observations indicate the spontaneous doping of the GaAs nanowires with both lead and silicon. These findings contribute to a deeper understanding of the VLS mechanism involved in nanowire growth. They are also an important step in the study of GaAs nanowire-doping processes.